STUDI LITERATUR PENINGKATAN HASIL BELAJAR MATEMATIKA SISWA DENGAN MODEL PEMBELAJARAN KOOPERTIF TIPE STAD - Winda Theressa Tambunan; W. L. Sihombing (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to find out that studying literature can effectively improve students' mathematics learning achievement with the STAD type cooperative learning model. The type of research used is research with a qualitative approach. Qualitative research uses descriptive or verbal data from people who have observed a behavior. The method used is literature study. Literature study is an activity that is closely related to the method of collecting library data, reading and taking notes as well as processing research materials. The type of data used is secondary data. Secondary data is data that already exists, so we just need to find and collect existing data. The secondary data source used in this research is student learning outcomes with the STAD type cooperative learning model. From the search results, the researchers found 7 journals relevant to the research topic. From the journal it was found that there was an increase in student learning outcomes using the STAD type cooperative learning model.